2011
DOI: 10.1007/s13233-011-0203-7
|View full text |Cite
|
Sign up to set email alerts
|

Freezing/thawing processing of PVA in the preparation of structured microspheres for protein drug delivery

Abstract: Drug stability and sustained release issues are important areas in drug-delivery research. The sustained release of proteins can be achieved by their encapsulation with a hydrophobic polymer, but this requires the proteins to be protected from the harsh processing environments of organic solvents and mechanical force. Preencapsulation with poly(vinyl alcohol) (PVA) using a freeze/thaw method has been shown to allow successful protection and sustained release. This study examined the effects of freezing/thawing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…To the best of our knowledge, there is no report available in the literature on the formation of physically cross‐linked cryogels from suspensions of PVA particles. However, cryogel formation through freeze‐thawing cycles of a PVA solution is well known . Cryogels were synthesized by chemical cross‐linking of PVA particles for this study.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, there is no report available in the literature on the formation of physically cross‐linked cryogels from suspensions of PVA particles. However, cryogel formation through freeze‐thawing cycles of a PVA solution is well known . Cryogels were synthesized by chemical cross‐linking of PVA particles for this study.…”
Section: Resultsmentioning
confidence: 99%
“…Among similar gel composites, cPVACGs filled with small particles of such biodegradable materials, allowing for the biomedical application of synthetic polyester, such as poly (lactide- co -glycolide) ( PLGA ), have been reported [ 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. When loaded with certain medicines, this disperse filler works primarily as a drug carrier, and the composite cryogel, as a whole, is used as a drug delivery and a controlled release system.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the drug release kinetics from this PLGA/PVA composite were virtually the same as that from the dexamethasone-loaded free PLGA particles, thus demonstrating the absence of significant diffusion hindrances induced by the macro-porous PVA-cryogel continuous phase with respect to drug release. In addition, it turned out that similar composites can also be used for the delivery of such well-water-soluble bioactive agents as pentamidine [ 53 ] or peptides (e.g., growth factors [ 58 ]), as well as some proteins (e.g., insulin [ 55 ] or serum albumin [ 56 ]).…”
Section: Introductionmentioning
confidence: 99%
“…PVA solutions may form hydrogels by a non‐toxic method called freezing–thawing (F‐T), which consists of consecutive cycles of freezing and thawing the polymer solutions . All mentioned properties together have led to the use of PVA‐based gels in a wide range of applications in the medical, pharmaceutical and packaging fields …”
Section: Introductionmentioning
confidence: 99%